2007
DOI: 10.1021/jp0676686
|View full text |Cite
|
Sign up to set email alerts
|

Improved Magnetic Anisotropy of Monodispersed Triangular Nickel Nanoplates

Abstract: Monodispersed triangular Ni nanoplates were successfully synthesized based on a facile thermal decomposition method. The Ni nanoplates have an average edge length of 15.4 nm, and their thickness is about 6 nm. Owing to high anisotropic structures, the Ni nanoplates exhibit typical ferromagnetic behaviors at room temperature. The blocking temperatures of the Ni nanoplates are over 400 and 226 K when the applied field is 100 and 500 Oe, respectively. Compared with bulk Ni, the Ni nanoplates exhibit significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 22 publications
4
57
1
Order By: Relevance
“…To overcome this problem, nonaqueous approaches have been developed as alternatives to aqueous systems. [9][10][11][12] The nonaqueous methods, however, often require a large amount of surfactants for controlling the growth and crystal size of the products. Furthermore, complex devices with protective atmosphere are needed to inject rapidly precursors into a hot organic reaction medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, nonaqueous approaches have been developed as alternatives to aqueous systems. [9][10][11][12] The nonaqueous methods, however, often require a large amount of surfactants for controlling the growth and crystal size of the products. Furthermore, complex devices with protective atmosphere are needed to inject rapidly precursors into a hot organic reaction medium.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, complex devices with protective atmosphere are needed to inject rapidly precursors into a hot organic reaction medium. [9][10][11][12] Another problem with hot injection is that the Ni nanoparticles prepared are usually amorphous 10 or poorly crystallized. 13,14 Additional treatment steps are therefore required to achieve good crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…12F) were synthesized by thermal decomposition of Ni(COOH) 2 in a mixed solution of OA, oleyl amine, and octadecene. 105 The small triangular nanoplate further grew along the [110] direction or connected along the [110] lateral plane, forming large triangular or hexagonal nanoplates. Ni nanorods with a diameter of 4 nm and a length of 15 nm (Fig.…”
mentioning
confidence: 99%
“…[10][11][12][13] These nanostructures have demonstrated increased magnetic and catalytic properties owing to their high shape anisotropy compared to their spherical counterparts. For example, nanoplatelets synthesised by Xu et al were found to have coercivities of up to 120 Oe at room temperature.…”
Section: Introductionmentioning
confidence: 99%